Kegiatan Penghijauan Sebagai Upaya Pelestarian Lingkungan Di Negeri Mamala, Kecamatan Leihitu, Maluku Tengah - Partini, Dwi; Helmi, Dewilna (Jurnal Pengabdian UntukMu NegeRI, 2023)
Climate change continues to occur uncontrollably, the earth's temperature is increasing. This condition can be caused by environmental degradation. Reforestation is an important step in maintaining the balance of the ecosystem and fighting the negative impacts of climate change. Through community service activities entitled greening, it aims to improve environmental conditions and increase awareness of the importance of nature conservation and environmental preservation. This activity was carried out as part of a collaborative effort between universities, local communities, and local governments in dealing with the challenges of environmental degradation in Mamala Country. As a result, various types of plants have been planted, such as trembesi, mahogany, mango, rambutan and durian.